HOTS (HIGH ORDER THINKING SKILL) DALAM TES BAHASA JERMAN - Eldaa Crystle Wenno; Kalvin Karuna (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2021)
In learning, students are trained to reason, analyze and evaluate to find solutions to problems faced. The way to conclude students' achievements in such behavior is a test. This study aims to describe the point of the German question (GER113 Main Problem Package) by asking the question whether the questions fall into the category of HOTS (Higher Order Thinking Skills). This research is a descriptive type of analytical and the object of analysis in this study is a package of German questions used in national examinations. The results showed that the German language test developed by the teacher was still dominated by the question item at a low cognitive level. This conclusion is based on the findings that there are 58.33% of LOTS category questions consisting of 4.16% of the level of wheezing (C1), 16.67% of understanding levels (C2), and 37.5% with applying levels (C3). Then for the HOTS category, there is 41.67% consisting of 37.5% analyze level (C4), 4.17% evaluate level (C5), and 0% creating level (C6).